2016
DOI: 10.1111/dmcn.13191
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculomegaly in very‐low‐birthweight infants with Down syndrome

Abstract: Very preterm infants with Down syndrome are at increased risk for ventriculomegaly (but not for IVH) compared with other infants born very preterm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…In the brain, we detected increased ventricular volumes, which is consistent with the trend observed in our previous study at PD29 (Llambrich, González, et al, 2022) and the ventriculomegaly typically observed in humans and mouse models for DS (Ishihara et al, 2010;Movsas et al, 2016;Pearlson et al, 1998;Raveau et al, 2017). However, we also detected increased hippocampal, cerebellar, and whole brain volumes in TS untreated mice that do not match clinical reports indicating reduced brain, hippocampal and cerebellar volumes in humans with DS (Aylward et al, 1997;Hamner et al, 2018;Patkee et al, 2020;Pearlson et al, 1998;Pinter et al, 2001;Rodrigues et al, 2019;Smigielska-Kuzia et al, 2011), and other preclinical studies that did not find brain volume differences in Ts65Dn mice (Aldridge et al, 2007;Duchon et al, 2021;Holtzman et al, 1996;Insausti et al, 1998).…”
Section: Structural Domainsupporting
confidence: 92%
“…In the brain, we detected increased ventricular volumes, which is consistent with the trend observed in our previous study at PD29 (Llambrich, González, et al, 2022) and the ventriculomegaly typically observed in humans and mouse models for DS (Ishihara et al, 2010;Movsas et al, 2016;Pearlson et al, 1998;Raveau et al, 2017). However, we also detected increased hippocampal, cerebellar, and whole brain volumes in TS untreated mice that do not match clinical reports indicating reduced brain, hippocampal and cerebellar volumes in humans with DS (Aylward et al, 1997;Hamner et al, 2018;Patkee et al, 2020;Pearlson et al, 1998;Pinter et al, 2001;Rodrigues et al, 2019;Smigielska-Kuzia et al, 2011), and other preclinical studies that did not find brain volume differences in Ts65Dn mice (Aldridge et al, 2007;Duchon et al, 2021;Holtzman et al, 1996;Insausti et al, 1998).…”
Section: Structural Domainsupporting
confidence: 92%
“…In the brain, we detected increased ventricular volumes, which is consistent with the trend observed in our previous study at PD29 (Llambrich, González, et al, 2022 ) and the ventriculomegaly typically observed in humans and mouse models for DS (Ishihara et al, 2010 ;Movsas et al, 2016 ;Pearlson et al, 1998 ;Raveau et al, 2017 ). However, we also detected increased hippocampal, cerebellar, and whole brain volumes in TS untreated mice that do not match clinical reports indicating reduced brain, hippocampal and cerebellar volumes in humans with DS (Aylward et al, 1997 ;Hamner et al, 2018 ;Patkee et al, 2020 ;Pearlson et al, 1998 ;Pinter et al, 2001 ;Rodrigues et al, 2019 ;Smigielska-Kuzia et al, 2011 ), and other preclinical studies that did not find brain volume differences in Ts65Dn mice (Aldridge et al, 2007 ;Duchon et al, 2021 ;Holtzman et al, 1996 ;Insausti et al, 1998 ).…”
Section: Structural Domainsupporting
confidence: 92%
“…Hydrocephalus, fetal ventriculomegaly (especially in very low birth weight infants < 1,500 g), and enlargement of the third ventricle, have been reported to occur in DS ( Farrell 1994 ; Schimmel et al. 2006 ; Movsas et al. 2016 ; Marano et al.…”
Section: Discussionmentioning
confidence: 99%